PENGARUH BRAND POSITIONING, BRAND IMAGE DAN BRAND TRUST TERHADAP REPURCHASE INTENTION PENGGUNA BUS TRANS BATAM - sheza Amelia; Tiurniari Purba (LPPM Universitas Putera Batam, 2025)
Public transportation plays a vital role in supporting community mobility. Trans Batam, a Bus Rapid Transit (BRT) system in Batam city, was developed to enhance connectivity across strategic areas and reduce traffic congestion. This study aims to analyze the effect of brand positioning, brand image and brand trust on repurchase intention among Trans Batam users. This research adopted a quantitative approach was adopted using an online survey distributed to 100 respondents in Batam City. The data were analyzed using validity and reliability tests, classical assumption test, multiple linear regression analysis, coefficient of determination and hypothesis testing. The results indicate that brand positioning does not have a significant individual effect on repurchase intention. Brand image shows a significant but negative effect, while brand trust also does not show a significant influence. However, all three variables simultaneously have a significant impact on repurchase intnention. These findings suggest that while each factor may not strongly influence use loyalty when considered separately, they collectively play a crucial role in shaping customers’ repurchase intention towards Trans Batam services. The coefficient of determination shows that the three variables contribute 6.5% to repurchase intention, with the rest influenced by other external factors.